THE RELIABILITY OF MARSHALL COMPACTOR FOR PREDICTING VOID AT REFUSAL DENSITY - Ida Rumkita; Siegfried Siegfried (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
In Indonesia the use of Marshall compactor has been applied widely for predicting void at refusal density especially in the provincial PU because the proper equipment for this purpose is rarely available. The main problem of using this equipment is the possibility of segregation that occurs during compaction process because of impact loading of Marshall equipment. The research carried out is to see the reliability of using Marshall compactor for predicting void at refusal density especially for the ACWC mixture. The are two types of ACWC gradation taken i.e. upper Fuller line and crosses Fuller line. By limited number of samples it is concluded that the Marshall compactor is still possible to use for ACWC upper Fuller line as shown by the gradation after compaction process still falls into specification of ACWC.